Studies on Lanthanide(III) Iodide Complexes of Some Schiff Bases - Gupta, Aarti; Agrawal, D.D.; Arora, Kishor (Asian Journal of Chemistry, 2010)
Some newly synthesized lanthanide(III) iodide complexes with Schiff bases having general composition LnL4I3 (Ln = La, Ce, Gd, Sm, and L = 2[N-(benzalidene) amino]pyridine (BAPy), 2[N-(4´-dimethylamino benzalidene)amino]pyridine (pBAPy); 2[N-(3´-nitrobenzalidene) amino]pyridine (3-NBAPy) and 2[N-(2´-hydroxybenzalidene) amino]pyridine (SAPy). pBAPy, 3-NBAPy and SAPy). These compounds were characterized on the basis of elemental analysis, molar conductance, molecular weight and spectral data. The coordination number six of central metal ion is proposed on the basis of conductance value.